Reconstruction of vanished cities - Nasirdinova Насирдинова; Джумамедиль Иманкулов; Дидар Алшоразов (Проект Байкал, 2024)
The preservation of historical heritage has the potential to act as a means of regenerative design in line with the concept of sustainable architecture. The idea of revitalising monuments is a tool to preserve and restore large green spaces and biodiversity. It is possible to create a multiplicative effect between historical and requested values of the contemporary environment: revival of dervish hotels – “hanakas” for digital nomads, wine taverns for tourists, craft workshops, gardens, art etc. to preserve crafts and natural environment, while participating in climate change mitigation.